Change in higher education: the psychological experience of facilitators and co-ordinators in a resource-based learning course - Holtzhausen, Sophia Maria (University of the Free State, 1999)
English: Higher Education in South Africa is currently being characterised by massification, globalisation, more non-traditional students entering the system, striving towards quality and cost-effective educational programmes, as well as a paradigm shift from lecture-based to resource-based learning (RBL) education (which is a learning methodology where the learning content is made accessible to students and the emphasis is shifted to the facilitator as the manager of knowledge and not the main source of knowledge). During the transformation of the South African higher education system, the ministry as well as various policy documents propose RBL as an appropriate delivery mode and a key principle to meet challenges (e.g. the expectations of the learners, the realities of the work place, and to maintain high standard graduates) posed to the university system. A profound understanding of the dynamics of a nation's higher educational change process is only possible when taking international developments into account. The evaluation of the experience of change is difficult, due to the complexity and pace of change in most higher education institutions. Change is affecting all facets of human experience. In this study attention is focused on the psychological experiences of facilitators and co-ordinators due to higher educational change in a RBL course. A quantitative and qualitative investigation was done to identify the presence of as well as the differences between the specific psychological experiences by facilitators and coordinators due to higher educational change (e.g. the paradigm shift to the RBL methodology). In this comparative study facilitators seem to be more concerned about the awareness, informational, personal, consequence and refocusing stages of concern, while the coordinators are more concerned about the management and collaboration stages of concern. These results correlate with the respective job descriptions of the facilitators and co-ordinators. In this study it is evident that both facilitators and co-ordinators have limited RBL knowledge and skills, due to their short involvement period in this delivery mode. The latter may be one of the reasons to clarify the presence of negative experiences of the self as regard coping with RBL by facilitators and co-ordinators. The facilitators' and co-ordinators' involvement in RBL was due to an obliged change, because they were nominated instead of volunteering. Therefore, this may implicate that the shift to RBL implies hard and difficult work for the developers, in order to equip staff with the necessary knowledge and skills of RBL. The majority of facilitators indicated that they are in favour of workshops. Only half of the co-ordinators were positive towards workshops, which indicates an important concern, if one takes into account that co-ordinators have to be subject experts who are responsible for the training and orientation of the facilitators and therefore need workshops/training opportunities to keep up with the latest developments regarding RBL. Both facilitators and co-ordinators demonstrated an increase in motivation, competency, and confidence levels, because they experience RBL as positive and effective. After six months there appears to be a difference between facilitators whose excitement levels were decreasing, while co-ordinators' excitement levels remained equal. The latter could be due to the fact that facilitators are more directly confronted with the RBL practice. There is also the tendency of high frustration levels amongst facilitators and co-ordinators which appear to be caused by the prominent problems in the South African context and the complexity of the Western culture of the students. A unique factor that complicates the implementation of RBL in the Resource-based Learning Career Preparation Programme is that staff are presenting and students are receiving education through a second-language medium. The above-mentioned perspectives and insights gained from the comparative study could guide both the developers and managers of the Resource-based Learning Career Preparation Programme to improve directly the psychological functioning of staff, and indirectly to improve the whole programme.

Afrikaans: Die Suid-Afrikaanse Hoër Onderwys word tans gekenmerk deur massifikasie, globalisering, die toename in toelating van nie-tradisionele studente, die strewe na kwaliteit en koste-effektiewe programme, asook die paradigmaskuif van lesinggebaseerde na brongebaseerde onderrig. Brongebaseerde onderrig verwys na 'n leermetodologie waar die leerinhoud aan die studente beskikbaar gestel word en beklemtoon die skuif na 'n fasiliteerder as bestuurder van kennis en nie die primêre bron van kennis nie. Gedurende die transformasie proses van die Suid-Afrikaanse hoër onderwyssisteem, het die ministerie asook verskeie beleidsdokumente brongebaseerde onderrig aanbeveel as 'n toepaslike metode om te voldoen aan die uitdagings (byvoorbeeld die verwagtings van die leerders, die realiteit van die werkplek, en om 'n hoë standaard gegradueerde studente te handhaaf) wat aan die hoër onderwyssisteem gestel word. Om "n diepgaande begrip van die dinamika van 'n nasie se hoër onderwysveranderingsproses te verkry, is slegs moontlik wanneer internasionale ontwikkeling in ag geneem word. Die ervaring van verandering is moeilik, as gevolg van die kompleksiteit en tempo van verandering in die meeste hoër onderwysinrigtings. Verandering beïnvloed alle fasette van die menslike ervaringswêreld. In hierdie studie is gefokus op die psigologiese ervarings van fasiliteerders en koordineerders as gevolg van hoër onderwysverandering in 'n brongebaseerde kursus. 'n Kwantitatiewe en kwalitatiewe ondersoek is geloods om die teenwoordigheid van en die verskille tussen spesifieke psigologiese ervanngs van fasiliteerders and koordineerders as gevolg van verandering in hoër onderwys (byvoorbeeld die paradigmaskuif na brongebaseerde onderrigmetodologie) te identifiseer. In hierdie vergelykende studie is fasiliteerders meer besorgd oor die bewuswording, inligting, persoonlike, gevolge, en herfokus fases van besorgdhede, teenoor die koordineerders wat meer besorg is oor die bestuur- en samewerkingsfases van besorgdheid. Hierdie resultate korreleer met die onderskeie werksbeskrywings van die fasiliteerders en koordineerders. In hierdie studie blyk dit dat beide die fasiliteerders en koordineerders oor beperkte brongebaseerde leerkennis en vaardighede beskik, as gevolg van die kort tydsperiode wat , hulle betrokke is by hierdie metode. Laasgenoemde kan ook een van die moontlike verklarings wees vir die teenwoordigheid van negatiewe ervarings van die self in terme van brongebaseerde onderrig by fasiliteerders en kcordineerders. Die fasiliteerders en koordineerders se betrokkenheid by brongebaseerde onderrig blyk 'n verpligte verandering te wees, omdat hulle genomineer is en nie vrywillig aangebied het me. Dus mag bogenoemde skuif na brongebaseerde onderrig moeilike take vir die programontwikkelaars impliseer ten einde die personeel met die nodige kennis en vaardighede ten opsigte van brongebaseerde leer toe te rus. Die meerderheid van die fasiliteerders het aangedui dat hulle ten gunste van werkswinkels is. Slegs die helfte van die koordineerders is positief ten opsigte van werkswinkels, wat 'n groot bekommernis is wanneer in ag geneem word dat koordineerders vakdeskundiges moet wees en verantwoordelik is vir die oriëntering en opleiding van fasiliteerders. Hulle benodig dus werkswinkels/opleidingsgeleenthede om op hoogte te bly van die nuutste ontwikkelinge aangaande brongebaseerde onderrig. Beide fasiliteerders en koordineerders het 'n toename in die motivering, bekwaamhede, en selfvertrouevlakke getoon omdat hulle brongebaseerde leer positief en effektief ervaar het. Na 'n tydperk van ses maande blyk daar 'n verskil te wees tussen die fasiliteerders, wie se vlakke van entoesiame gedaal het, teenoor die koordineerders wie se vlakke van entoesiasme konstant gebly het. Laasgenoemde kan toegskryf word aan die feit dat die fasiliteerders meer direk gekonfronteer word deur die brongebaseerde leerpraktyk. Daar blyk ook 'n geneigdheid tot hoë frustrasievlakke by fasiliteerders en koordineerders aanwesig te wees, wat moontlik toegeskryf kan word aan prominente probleme binne die Suid-Afrikaanse konteks, en die kompleksiteit van die Westerse kultuur van die studente. 'n Unieke faktor wat die implementering van brongebaseerde onderrig in die Brongebaseerde Onderrigprogram meer kompleks maak, is die feit dat die personeel se aanbieding asook die studente se verkryging van opleiding deur middel van 'n tweede taalmedium geskied. Bogenoemde perspektiewe en insigte wat by wyse van die vergelykende studie bekom is, kan die ontwikkelaars en bestuurders van die program lei om op 'n direkte wyse die psigologiese funksionering van personeel en op 'n indirekte wyse die totale program te verbeter.
Keywords: Resource-based learning; Paradigm shift; Facilitator; Co-ordinator; Psychological experience; Education, Higher -- Psychological aspects -- South Africa; Educational change -- South Africa; Teaching -- Psychological aspects; Counseling; Dissertation (M.Soc.Sc. (Psychology))--University of the Free State, 1999